A Model of Search with Two Stages of Information Acquisition and Additive Learning - Gibbard, Peter (Management Science, 2022)
This paper presents a model of choice with two stages of information acquisition. In this model, the choice problem can be interpreted as a variant of a more general multiarmed bandit problem. We assume that information acquisition takes a simple “additive form”—the value of an alternative is the sum of two components, which the decision maker can learn by undertaking two stages of information acquisition. This assumption yields a model that is tractable for the purposes of structural estimation. One possible application of the model is to online purchasing on e-commerce sites. For a consumer on an e-commerce website, there are potentially two stages of information acquisition: the consumer can obtain information about an alternative from (i) browsing the search results page and (ii) clicking on the alternative. By way of contrast, in much of the literature on structural econometric models of online purchasing, there is typically only one stage of information acquisition. Our paper may, therefore, provide a more realistic theory for modeling search, at least for those types of search—such as online purchasing—that involve two stages of information acquisition. This paper was accepted by Manel Baucells, behavioral economics and decision analysis.